Rutin electrochemical sensing electrode material based on Au-ZrO2 material, preparation method of rutin electrochemical sensing electrode material and sensor

By modifying the Au@ZrO2 nanostructure on the electrochemical sensing electrode, the problem that the existing technology cannot efficiently and in real time detect the rutin content in fruits and vegetables is solved, and a high sensitivity and low cost detection effect is achieved.

CN119881042AActive Publication Date: 2025-04-25TARIM UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510017981.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-25
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing detection methods cannot simultaneously detect the rutin content in fruits and vegetables efficiently and in real time, and there are problems such as low sensitivity, high cost and complex operation.

Method used

The rutin electrochemical sensing electrode material based on Au-ZrO2 material is used to modify the Au@ZrO2 nanostructure on the electrode, and its internal band gap is regulated to improve the detection performance of rutin.

Benefits of technology

It realizes high sensitivity detection of rutin, with a wide linear range, low detection limit, good sensing performance, simple preparation process, easy raw materials, and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119881042A_ABST
    Figure CN119881042A_ABST
Patent Text Reader

Abstract

The invention provides a rutin electrochemical sensing electrode material based on an Au-ZrO2 material, a preparation method of the rutin electrochemical sensing electrode material and a sensor, and belongs to the technical field of electrochemical detection. The preparation method of the electrode material comprises the following steps: S1, mixing and stirring zirconium chloride, urea, ethylene glycol and absolute ethyl alcohol to obtain a mixed solution; s2, reacting the mixed solution in a reaction kettle to obtain a reaction material; s3, sequentially carrying out centrifugal separation, washing, drying, calcining and grinding on the reaction material to obtain zirconium oxide; s4, zirconium oxide, sodium dodecyl benzene sulfonate, sodium borohydride, a chloroauric acid solution and absolute ethyl alcohol are mixed and stirred and then react, and the rutin electrochemical sensing electrode material based on the Au-ZrO2 material is obtained. According to the invention, the semiconductor material ZrO2 nanostructure is added into the Au nanoparticles for the first time to carry out regulation and control research on the internal band gap so as to detect the rutin substance, and the sensor is good in sensing performance, wide in linear range, low in detection limit and relatively high in sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical detection, and particularly relates to a rutin electrochemical sensing electrode material based on Au-ZrO2 material, a preparation method thereof, and a sensor. Background Art

[0002] Rutin is a pure natural plant extract, widely found in fruits and vegetables such as dates, apricots, apple rue leaves, tobacco leaves, orange peels, tomatoes, buckwheat flowers, etc. It has a natural antioxidant effect. 1. It can be used as an edible antioxidant and nutritional enhancer. 2. It has anti-inflammatory effects, can reduce inflammation caused by mustard oil on animal eyes or skin, and has antiviral effects. 3. It has the effects of maintaining vascular resistance, reducing its permeability, and reducing brittleness. It can be used to prevent and treat diseases such as cerebral hemorrhage, hypertension, retinal hemorrhage, purpura and acute hemorrhagic nephritis.

[0003] According to existing reports, UV-visible spectrophotometry, capillary electrophoresis, and high-performance liquid chromatography have been used for the detection of rutin. Although these methods are highly accepted, they require complex pretreatment, lack the necessary specificity, are time-consuming, and are costly, so they cannot achieve simultaneous detection and real-time monitoring. The components of the actual fruits and vegetables tested are complex, the sensitivity of chromatography detection is not high, the detection cycle is long, and the selectivity is poor. Although spectrophotometry is simple to operate, it is labor-intensive, the sensitivity is not high, and the accuracy needs to be improved. Capillary electrophoresis has the advantage of requiring less sample, but the detection process is time-consuming and labor-intensive, and the reproducibility needs to be improved. Electrochemical sensing technology has been widely used this year, has developed rapidly, and has a lot of technical support. And it is currently less used in the field of rutin detection.

[0004] Electrochemical methods have the advantages of high sensitivity, fast reaction speed, real-time monitoring, portability, and simple operation. In particular, the equipment is portable and can be used for on-site detection. In recent years, with the deployment of the country's health development strategy and people's increasing attention to health, food safety, and environmental science, it is particularly important to use electrochemical sensing technology for simultaneous detection and real-time monitoring of rutin in industrial production.

[0005] Therefore, in order to detect the rutin content in fruits and vegetables and provide technical support for the development of the fruit and vegetable industry, it is urgent to develop an efficient, convenient and low-cost detection method for the detection of the flavonoid rutin. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a rutin electrochemical sensing electrode material based on Au-ZrO2 material, a preparation method thereof, and a sensor. The present invention is the first to use the semiconductor material ZrO2 nanostructure to add Au nanoparticles to conduct research on the regulation of its internal band gap for the detection of rutin substances, with good sensing performance, wide linear range, low detection limit and high sensitivity.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] In a first aspect, a method for preparing a rutin electrochemical sensing electrode material based on Au-ZrO2 material comprises the following steps:

[0009] S1. The zirconium chloride, urea, ethylene glycol and anhydrous ethanol are mixed and stirred to obtain a mixed solution;

[0010] S2. The mixed solution is reacted in a reactor to obtain a reaction material;

[0011] S3. The reaction material is sequentially centrifuged, washed, dried, calcined, and ground to obtain zirconium oxide;

[0012] S4. Mix zirconium oxide, sodium dodecylbenzenesulfonate, sodium borohydride, chloroauric acid solution and anhydrous ethanol, stir and react to obtain a rutin electrochemical sensing electrode material based on Au-ZrO2 material.

[0013] In the present invention, ZrO2 can provide more reactive sites and has a stable structure due to its special nanostructure, and can make Au nanoparticles better composited therein. Gold nanoparticles have the advantages of good conductivity and large active area, so they can meet the electrochemical detection of rutin.

[0014] Preferably, the mass volume ratio of zirconium chloride, urea, ethylene glycol and anhydrous ethanol in S1 is 0.23-0.35 g: 0.1-0.2 g: 30-50 ml: 30-50 ml.

[0015] Preferably, the reaction temperature in S2 is 170-190° C., and the reaction time is 10-16 h.

[0016] Preferably, the drying temperature in S3 is 110-130° C. and the drying time is 10-16 h.

[0017] Preferably, the calcination time in S3 is 450-550° C. for 1-3 hours.

[0018] Preferably, the volume mass ratio of zirconium oxide, sodium dodecylbenzenesulfonate, sodium borohydride, chloroauric acid solution and anhydrous ethanol in S4 is 0.1-0.2g: 0.2-0.3g: 0.02-0.04g: 2.5-4ml: 60-80ml.

[0019] Preferably, the reaction temperature in S4 is 110-130° C. and the reaction time is 3-5 h.

[0020] In a second aspect, the present invention provides a rutin electrochemical sensing electrode material based on Au-ZrO2 material, which is prepared by the above method.

[0021] In a third aspect, the present invention provides a method for preparing a rutin electrochemical sensor based on Au-ZrO2 material, comprising the following steps:

[0022] Polish the GCE electrode;

[0023] The polished GCE was tested by cyclic voltammetry in a solution of 5mM K3[Fe(CN)6], 5mM K4[Fe(CN)6] and 0.1M KCl, with a scan rate of 100mV and a potential region of -0.2-0.6V. When the potential difference between the oxidation peak and the reduction peak was less than 100mV, the electrode polishing was completed.

[0024] The rutin electrochemical sensor electrode material, ethanol, ultrapure water and 0.5% naphthol are mixed and then ultrasonically dispersed to obtain a dispersion;

[0025] The dispersion was dripped onto the polished surface of the GCE electrode and naturally air-dried to obtain a sensor for high-performance detection of luteolin.

[0026] Preferably, the mass volume ratio of the rutin electrochemical sensor electrode material, ethanol, ultrapure water, and 5% naphthol is 1 mg: 300 uL: 700 uL: 10 uL;

[0027] The amount of the dispersion is 5uL / cm 2 .

[0028] Beneficial technical effects:

[0029] The present invention uses the semiconductor material ZrO2 nanostructure to add Au nanoparticles for the first time to study the regulation of its internal band gap for the detection of rutin. At the same time, the successfully prepared Au@ZrO2 material modified electrode has a good detection effect on rutin. The electrode material preparation process is simple, the raw materials are easy to obtain, the preparation method is simple and reliable, and the prepared sensor electrode has good sensing performance, a wide linear range, a low detection limit, and a high sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The XRD patterns of the sensing materials obtained in Example 1 and Comparative Example 1 are shown below;

[0031] Figure 2 The SEM images of the sensing materials obtained in Example 1 and Comparative Example 1;

[0032] Figure 3 The CV curve of the sensor prepared by the sensing material of Example 1 detecting luteolin;

[0033] Figure 4 This is a performance test diagram of the sensor prepared with the sensing material of Example 1 for detecting luteolin. DETAILED DESCRIPTION

[0034] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0035] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] The "room temperature" and "normal temperature" mentioned in the present invention are all calculated as 25±2°C unless otherwise specified.

[0040] The raw materials and instruments used in the following examples of the present invention are commercially available unless otherwise specified.

[0041] Example 1

[0042] This embodiment provides a rutin electrochemical sensing material based on Au-ZrO2 material, and the preparation steps are as follows:

[0043] S1. 0.23 g zirconium chloride, 0.1 g urea, 30 ml ethylene glycol and 30 ml anhydrous ethanol were mixed and stirred, and the mixture was placed on a magnetic stirrer and stirred vigorously to completely dissolve the mixture;

[0044] S2. The mixture was transferred to a 100 mL stainless steel autoclave coated with polytetrafluoroethylene and reacted at a temperature of 180 ° C for 12 hours to obtain a reaction material;

[0045] S3. The reaction material was naturally cooled to obtain an off-white product, which was then centrifuged, washed with distilled water and ethanol 5 times, and finally dried at a constant temperature of 120°C for 12h; the product was then calcined in a tubular furnace at 500°C for 2 hours and ground to obtain zirconium oxide;

[0046] S4. Mix 0.1g zirconium oxide, 0.2g sodium dodecylbenzenesulfonate, 0.02g sodium borohydride, 2.5ml chloroauric acid solution and 60ml anhydrous ethanol in a glass beaker, place a magnetic stirrer and stir at room temperature at an appropriate speed to completely dissolve it; then place the mixture in an oven at 120°C to react for 4h to obtain a rutin electrochemical sensor material based on Au-ZrO2 material.

[0047] Example 2

[0048] This embodiment provides a rutin electrochemical sensing material based on Au-ZrO2 material, and the preparation steps are as follows:

[0049] S1. 0.28 g zirconium chloride, 0.15 g urea, 40 ml ethylene glycol and 40 ml anhydrous ethanol were mixed and stirred, and the mixture was placed on a magnetic stirrer and stirred vigorously to completely dissolve the mixture;

[0050] S2. The mixture was transferred to a 100 mL stainless steel autoclave coated with polytetrafluoroethylene and reacted at a temperature of 170 ° C for 16 hours to obtain a reaction material;

[0051] S3. The reaction material was naturally cooled to obtain an off-white product, which was then centrifuged, washed with distilled water and ethanol for 5 times, and finally dried at a constant temperature of 110°C for 10 hours; the product was then calcined in a tubular furnace at 450°C for 2 hours, and ground to obtain zirconium oxide;

[0052] S4. Mix 0.15g zirconium oxide, 0.3g sodium dodecylbenzenesulfonate, 0.03g sodium borohydride, 3ml chloroauric acid solution and 70ml anhydrous ethanol in a glass beaker, place a magnetic stirrer and stir at room temperature at an appropriate speed to completely dissolve it; then place the mixture in an oven at 110°C to react for 5h to obtain a rutin electrochemical sensor material based on Au-ZrO2 material.

[0053] Example 3

[0054] This embodiment provides a rutin electrochemical sensing material based on Au-ZrO2 material, and the preparation steps are as follows:

[0055] S1. 0.35 g zirconium chloride, 0.2 g urea, 50 ml ethylene glycol and 50 ml anhydrous ethanol were mixed and stirred, and the mixture was placed on a magnetic stirrer and stirred vigorously to completely dissolve the mixture;

[0056] S2. The mixture was transferred to a 150 mL stainless steel autoclave coated with polytetrafluoroethylene and reacted at a temperature of 190 ° C for 12 hours to obtain a reaction material;

[0057] S3. The reaction material was naturally cooled to obtain an off-white product, which was then centrifuged, washed with distilled water and ethanol 5 times, and finally dried at a constant temperature of 130°C for 16 hours; the product was then calcined in a tubular furnace at 550°C for 2 hours and ground to obtain zirconium oxide;

[0058] S4. Mix 0.1g zirconium oxide, 0.3g sodium dodecylbenzenesulfonate, 0.04g sodium borohydride, 4ml chloroauric acid solution and 80ml anhydrous ethanol in a glass beaker, place a magnetic stirrer and stir at room temperature at an appropriate speed to completely dissolve it; then place the mixture in an oven at 130°C to react for 5h to obtain a rutin electrochemical sensor material based on Au-ZrO2 material.

[0059] Experimental Example 1

[0060] XRD spectrum analysis:

[0061] like Figure 1 As shown, the peaks of synthesized ZrO2 at 29.2°, 33.8°, 48.8°, 58.0°, 61.0° and 72.4° can be attributed to (101), (200), (220), (211), (222) and (400) crystal plane peaks, which are consistent with the crystal structure of nano ZrO2 (corresponding card PDF#89-6976). The characteristic crystal peaks of gold all appear in the Au@ZrO2 composite material, and the (101) peak of ZrO2 shifts slightly to the right, indicating that there is a strong interaction between Au and ZrO2 in the composite material.

[0062] Experimental Example 2

[0063] Structural characterization:

[0064] like Figure 2As shown in the figure, ZrO2 material is an aggregate composed of nanoparticles (a). These aggregates are composed of a large number of nano-sized particles, ranging in size from 10nm to 60nm. The scanning electron microscope and transmission electron microscope of the Au@ZrO2 composite material are shown in Figure b and Figure c respectively. It is very prominent that Au nanoparticles grow effectively on the spherical ZrO2 nanostructure. It shows good uniform particle dispersion. (b). The average size of Au nanoparticles is about 2.35 nanometers (c). The ZrO2 nanostructure undergoes obvious structural changes. This structural change can be attributed to the addition of Au nanoparticles, which changes its original growth trend during the growth of the crystal. And this change in its crystal growth mode can theoretically provide more active sites in the detection of catalytic reactions. And the addition of Au nanoparticles itself promotes the catalytic process, because Au nanoparticles themselves have good conductivity and catalytic function. The combination of the two enhances the electrochemical catalytic effect.

[0065] Experimental Example 3

[0066] Sensing material detection rutin performance test

[0067] 1. Preparation of sensing materials for high-performance detection of rutin

[0068] Electrode polishing:

[0069] The GCE electrode was polished with 0.3μm and 0.05μm Al2O3 powders to remove the oxide layer on the electrode surface, and the polished GCE was tested by cyclic voltammetry in a solution of 5mM K3[Fe(CN)6], 5mM K4[Fe(CN)6] and 0.1M KCl, with a scan rate of 100mV and a potential region of -0.2-0.6V. The electrode polishing was completed when the potential difference between the oxidation peak and the reduction peak was less than 100mV.

[0070] Sensing material and polished electrode composite:

[0071] 1 mg of Au@ZrO2 obtained in Example 1 was mixed with 400 μL ethanol, 600 μL ultrapure water and 10 μL naphthol (5%) and then ultrasonicated. Subsequently, 5 μL of the resulting solution was carefully applied to the original electrode surface by dispersive titration and allowed to air dry naturally to obtain a rutin electrochemical sensor based on Au-ZrO2 material.

[0072] At the same time, GCE sensors without any modification and ZrO2 / GCE sensors were prepared.

[0073] Electrochemical sensing technology detection: Differential pulse voltammetry (DPV) was used to study the response electrochemical signals of rutin on different electrodes. No obvious DPV response was observed on the bare GCE surface at 100nM rutin, indicating that the oxidation of rutin on the bare GCE surface was very small or had no catalytic effect. In contrast, the response signal measured on ZrO2 / GCE was 0.99μA. A stronger response signal of 4.89μA was detected on Au@ZrO2 / GCE, with a higher rutin response signal. When scanning the potential from 0V to 0.8V at 100mV / s, rutin was oxidized to ketones with similar structures.

[0074] Relationship between electrode response and pH: The DPV oxidation peak current under Au@ZrO2 / GCE was studied in the presence of BR buffer with pH increasing from 2 to 6.5. The DPV oxidation potential shifted negatively from 0V to 0.8V. In BR solution with a pH of 3, the DPV rutin peak current of Au@ZrO2 was the highest, which was 20.82μA. In general, the oxidation of rutin on the electrode surface is mainly a deprotonation process, which is affected by two key factors. High hydrogen ion concentration can inhibit the reaction by increasing the hydrogen ion concentration of the reaction product, while reducing hydrogen ions can enhance the oxidation reaction but may also reduce the catalytic performance of the electrode. When these opposing factors are balanced, the reaction rate on the electrode surface reaches a peak, producing the maximum DPV signal, and the peak current of DPV reaches a maximum at a pH of 3.

[0075] Actual fruit and vegetable testing:

[0076] The Kuche small white apricot juice was diluted 2000 times and then subjected to differential pulse voltammetry.

[0077] The actual cherry tomato sample was measured. After the juice was diluted 2000 times, the above-mentioned differential pulse voltammetry measurement was also performed.

[0078] Using Au@ZrO2 / GCE as the working electrode, after 5 rounds of testing, the average concentrations of rutin in small white apricot juice and cherry tomato juice were 1.83 and 3.28 nM, respectively.

[0079] In order to improve the reliability of detection, the standard addition method was used to determine the recovery rate of rutin identified by the electrode in solution. After rutin was added at concentrations of 100nM, 200nM, and 300nM, the detection recovery rate was always close to 100% (99.78-100.5% in small white apricot juice and 99.79-101.2% in cherry tomato juice), and the relative standard deviation of each subsequent measurement after addition remained low (1.1%-3.2%).

[0080] 2. Linear relationship detection

[0081] like Figure 3 As shown in a, when the Au@ZrO2 / GCE electrode prepared by the present invention detects 100nM rutin (dissolved in BR buffer, pH: 3), the cyclic voltammetry (CV) curve shows regular changes in the redox signal as the scan rate increases, the redox peak intensity gradually increases, the oxidation peak potential moves to the right, and the reduction peak potential moves to the left. The peak voltage and the logarithm of the scan rate show a linear relationship ( Figure 3 b), the charge transfer coefficient is calculated to be 0.57, and the charge transfer number is 2.3, which indicates that the redox process of rutin on Au@ZrO2 / GCE is a two-electron two-proton process.

[0082] 3. Sensitivity and detection limit detection

[0083] like Figure 4 As shown in Fig. a, the differential pulse voltammetry (DPV) response of the Au@ZrO2 / GCE electrode prepared in the present invention to different concentrations of rutin (dissolved in BR buffer, pH: 3). The relationship between the corresponding DPV peak current and concentration is shown in Fig. Figure 4 As shown in b, the DPV peak current showed a linear correlation with luteolin in the concentration ranges of 0.1-50nM and 50-3600nM, respectively. The overall linear range was: 0.1-3600nM. The highest sensitivity of detection was 109.64uA / uM, and the detection limit was 0.6nM.

[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a rutin electrochemical sensing electrode material based on Au-ZrO2 material, characterized in that: The following steps are involved: S1. The zirconium chloride, urea, ethylene glycol and anhydrous ethanol are mixed and stirred to obtain a mixed solution; S2. The mixed solution is reacted in a reactor to obtain a reaction material; S3. The reaction material is sequentially centrifuged, washed, dried, calcined, and ground to obtain zirconium oxide; S4. Mix zirconium oxide, sodium dodecylbenzenesulfonate, sodium borohydride, chloroauric acid solution and anhydrous ethanol, stir and react to obtain a rutin electrochemical sensing electrode material based on Au-ZrO2 material.

2. The preparation method according to claim 1, characterized in that: The mass volume ratio of zirconium chloride, urea, ethylene glycol and anhydrous ethanol in S1 is (0.23-0.35) g: (0.1-0.2) g: (30-50) ml: (30-50) ml.

3. The preparation method according to claim 1, characterized in that: The reaction temperature in S2 is 170-190° C., and the reaction time is 10-16 h.

4. The preparation method according to claim 1, characterized in that: The calcination time in S3 is 450-550° C. for 1-3 hours.

5. The preparation method according to claim 1, characterized in that: The volume mass ratio of zirconium oxide, sodium dodecylbenzenesulfonate, sodium borohydride, chloroauric acid solution and anhydrous ethanol in S4 is (0.1-0.2) g: (0.2-0.3) g: (0.02-0.04) g: (2.5-4) ml: (60-80) ml.

6. The preparation method according to claim 1, characterized in that: The reaction temperature in S4 is 110-130° C. and the reaction time is 3-5 h.

7. A rutin electrochemical sensing electrode material based on Au-ZrO2 material, characterized in that: The method is prepared by any one of claims 1 to 6.

8. A method for preparing a rutin electrochemical sensor based on Au-ZrO2 material, characterized in that: The following steps are included Polish the GCE electrode; The rutin electrochemical sensor electrode material according to claim 1, ethanol, ultrapure water, and 0.5% naphthol are mixed and ultrasonically dispersed to obtain a dispersion; The dispersion was dripped onto the polished surface of the GCE electrode and naturally air-dried to obtain a sensor for high-performance detection of luteolin.

9. The preparation method according to claim 8, characterized in that: The mass volume ratio of the rutin electrochemical sensor electrode material, ethanol, ultrapure water, and 5% naphthol is 1 mg: 300 uL: 700 uL: 10 uL; The amount of the dispersion is 5uL / cm 2 .

Citation Information

Patent Citations

  • Preparation of nano zircite powder

    CN101412537A

  • Rutin testing method adopting boron doped graphene supported gold core gold platinum alloy shell nanocomposite modified electrode

    CN106290506A

  • Large-specific-surface porous zirconium dioxide mesoscopic crystal, preparation method thereof and application

    CN106622200A

  • Composite zirconia powder used for oxygen sensor

    CN108467264A

  • Method for preparing gold nano cage modified electrode and detecting rutin content

    CN109164150A